TEORI MEDIA/TEORI DIFUSI INOVASI - Mailin Mailin; Gepeng Rambe; Abdi Ar-Ridho; Candra Candra (JGK (Jurnal Guru Kita), 2022)
This study aims to examine the theory of diffusion of innovation, the method of this research is library research, the results of this study are: The process of adopting innovation through several stages so that there is a public decision to accept and reject innovation. 1. The knowledge stage where the community obtains a number of information or knowledge, functions, benefits and various things regarding innovation from various information channels, including: friends, family, neighbors, and the mass media. 2. Then the community began to give both positive and negative attitudes, here there was a search for additional information from various communication channels. Communication channels make a big enough contribution to the spread of innovation to the community, interpersonal communication channels are more commonly found when there is a spread of innovation. 3. Next is the decision stage, namely the decision to adopt or reject the innovation, so that in the decision process there are people who adopt, that is, fully use the innovation and some reject the innovation. In making decisions, people tend to consider the relative advantages of innovation, which can be seen from the speed of healing, low and affordable costs, the suitability of the innovation to the needs of the community, as evidenced by observations by other people regarding the advantages of innovation, location affordability and perceptions of information. 4. The implementation stage is that people who choose to adopt will carry out their decisions by coming to the treatment of sangkal putung, on the other hand, people who refuse will also carry out the decisions they have chosen. 5. The last stage is the confirmation process in which the community assesses that the chosen decision is correct or not.